Desarrollo de la motricidad fina con la aplicación de estrategias virtuales en los niños de educación inicial de la Unidad Educativa Isidro Ayora del cantón Ventanas Provincia de Los Ríos - Acosta Enríquez, Paola Cecilia (2022)
In the present case study, the research topic is virtual strategies for the importance of fine motor skills in children of initial education "Isidro Ayora" and presents the impact that fine motor skills generated through the virtual modality considering that the techniques and the use of teaching materials will help in the comprehensive development of children and in turn acquiring results that are satisfactory within the field of virtual education. Fine motor skills are very important since they help the infant to develop their abilities and skills through the application of methodological strategies taught by the teacher, in fact the appropriate techniques help to contribute to the strengthening and wisdom of children of early childhood together to the teaching and learning process. Of equal importance, the family is integrated in a fundamental way in the development and skills that the child will achieve during his learning process that will allow him to carry out thanks to his knowledge induced by his teacher. In the same way that the present case study has as its purpose the application of virtual strategy techniques for fine motor skills, achieving its objective that the infant maintains his spirituality of learning and satisfying his knowledge from early childhood with the help or guideline of the teacher. Who will be your guide in this teaching process that will be carried out in your academic knowledge during your school stage and your development in personal and social interaction.